Biochemical Parameters in Confirmed Covid-19 Patients: A Hospital Based Study from Eastern Nepal - Niraula, A.; Gelal, B.; Lamsal, M.; Karki, D.; Chhetri, R. (Kathmandu University Medical Journal, 2021)
Background COVID-19 has posed a global threat to almost every part of the world. The disease has varied form of presentation and the modern medicine has still not been able to provide definite treatment for the disease.Objective To assess the biochemical parameters in confirmed patients of COVID-19 admitted at B.P. Koirala Institute of Health Sciences (BPKIHS), Dharan, Nepal.Method This is a retrospective hospital based cross-sectional study conducted in the Department of Biochemistry, B.P. Koirala Institute of Health Sciences, Dharan from October to December, 2020. Convenient sampling technique was used to enroll the data of the patients for whom the biochemical parameters were requested by the clinicians. Routine biochemical tests were performed in Cobas c311 autoanalyzer.Result A total of 202 patients with confirmed COVID-19 infections and admitted at COVID Hospital, BPKIHS were enrolled. The findings depict an elevated liver enzyme (alanine aminotransferase, aspartate aminotransferase, alkaline phosphatase, gamma glutamyl transpeptidase and cardiac enzymes (creatine kinase-total and creatine kinase- MB) in the study population. Increased serum ferritin (1026.08±220.53), hs CRP (41.52±5.22) and lactate dehydrogenase 360 [303.50-526.75] was found in the patients. Also, majority of the patients (> 50%) had abnormal biochemical findings. Conclusion Biomarkers like C-reactive protein, lactate dehydrogenase and ferritin have shown significant clinical implications in effective management, monitoring, and assessment of the severity of disease in COVID- 19 patients. Simple and cost-effective markers like CRP, LDH, HbA1c could be used for monitoring the severity of COVID-19 infection.